2018
DOI: 10.1159/000489394
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Complications after Endoscopic Mucosal Biopsy

Abstract: Background: There is no clarity with regard to the occurrence of serious complications from EGD-driven mucosal biopsy. This is important for considering both clinically indicated procedures and mucosal sampling for research. Methods: We sought to quantify rates of serious complications from esophagogastroduodenoscopy (EGD) with biopsy. We studied 13,233 patients undergoing outpatient EGD with biopsy over 5 years in 2 North Dakota community hospitals, based on the reasoning that serious complications would caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…9 Similarly, in a 2018 retrospective analysis of over 13,000 EGDs with biopsy sampling, no perforations occurred within 30 days of the index procedure. 19 These contemporary estimates are similar in magnitude but even more encouraging than prior estimates of perforation risk ranging between 1 in 2500 and 1 in 11,000 3 that were based on considerably older studies. 20,21…”
Section: Perforationmentioning
confidence: 59%
See 1 more Smart Citation
“…9 Similarly, in a 2018 retrospective analysis of over 13,000 EGDs with biopsy sampling, no perforations occurred within 30 days of the index procedure. 19 These contemporary estimates are similar in magnitude but even more encouraging than prior estimates of perforation risk ranging between 1 in 2500 and 1 in 11,000 3 that were based on considerably older studies. 20,21…”
Section: Perforationmentioning
confidence: 59%
“…The ASGE guideline on the management of antithrombotic agents for endoscopy describes both PEG and PEJ as highrisk procedures overall and recognizes that aspirin alone does not portend an increased risk of bleeding. 19 Risk factors associated with a higher risk of bleeding after PEG placement are as follows:…”
Section: Egd With Gastrostomy or Jejunostomy Tube Placement Bleedingmentioning
confidence: 99%
“…However, these guidelines were mainly intended to diagnose advanced GC, not early GC. Although many studies concluded that antithrombotics did not increase risk of bleeding 18 19 , biopsy can cause local fibrosis, which may make endoscopic treatment difficult. As most early GC now can be effectively treated by endoscopy 20 , this might become a major problem.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio de 13,233 pacientes sometidos a endoscopia superior a los que se les realizó biopsia de la mucosa no se reportó hemorragia o perforación. Estos datos confirman que el riesgo/beneficio de realizar una biopsia es favorable 43 . Sin embargo, hasta el momento no existen estudios que evalúen la seguridad de la toma de biopsias de la mucosa en pacientes tratados con los nuevos antiplaquetarios (prasugrel, ticagrelor, vorapaxar) o ACOD.…”
Section: Bajo Riesgo De Hemorragiaunclassified